Perception-driven dynamics of mimicry based on attractor field model - Brejcha, Jindřich; Tureček, Petr; Kleisner, Karel (Interface focus, 2021)
We provide a formal account of an interface that bridges two different levels of dynamic processes manifested by mimicry: prey-prey interactions and predators' perception. Mimicry is a coevolutionary process between an animate selective agent and at least two similar organisms selected by agent's perception-driven actions. Attractor field model explains perceived similarity of forms by noting that in both human and animal cognition, morphologically intermediate forms are more likely to be perceived as belonging to rare rather than abundant forms. We formalize this model in terms of predators' perception space deformation using numerical simulations and argue that the probability of confusion between similar species creates pressure on the perception space, which in turn leads to inflation of regions of perception space with high density of species representations. Such inflation causes increased discrimination between species by a predator, which implies that adaptive mimicry could initially emerge more easily among atypical species because they do not need the same level of similarity to the model. We provide a theoretical instrument to conceptualize interdependence between objective measurable matrices and perceived matrices of the same external reality. We believe that our framework leads to a more precise understanding of the evolution of mimicry.
Keywords: Müllerian mimicry; Batesian mimicry; frequency dependence; behaviour; agency; similarity